A incidência da Síndrome de Burnout nas atividades profissionais de Auditores Tributários Públicos do Estado do Paraná - Silva, Moacir Borges da (2021)
The present research approaches burnout syndrome which comes from professional exercise in a troubled and stressful context between the professional and his peers in the work environment, resulting in emotional, psychological and physical imbalances. What has generated alerts by medicine because it is a public health problem on all continents, having the constant action of the World Health Organization (WHO), which through the 11th Revision of the International Classification of Diseases (ICD-11), which comes into force in January 2022, recognizes the pathology as a phenomenon associated with employment and classification with coding QD85 Burnout. The present study has as a general objective to know the phenomena experienced by the tax auditors of the Paraná State Revenue Service, which may be, to some degree, affected by burnout syndrome and as specific objectives, to mensure the collected data and the reliability of the inventory used, the MBI - GS Maslach Burnout Inventory - General Survey, proposedby (Schaufeli, Leiter, Maslach & Jackson, 1996) and to identify the perceived effects on physical and emotional health, manifested by the measured levels of Burnout Syndrome, in the public tax auditors of the Paraná State Revenue Service. The research was developed using the descriptive study with quantitative approach, with the return of 200 respondents through a digital platform, with an online application. Data collection occurred by the following instruments: Sociodemographic data; Characteristics of the work; Perception of work and MBIGS - Burnout Maslach Inventory - General Survey, used for service professions in general, proposed in three dimensions: emotional exhaustion, cynicism and personal accomplishment, with 16 items, and the measurement was performed by the likert table with frequencies of (0-6), being zero never and six every day. The data were rotated in the SPSS - Solution of Products and Services of Statistics and the analysis of the results is considered positive, because they have internal consistency, reliability and validity, since cronbach's alpha (0.770) fits the range accepted by the literature (0.70 -0.90). The Anova (0.000), KMO (0.886) and Bartlet (0.000) tests are also robust and print statistical significance of the data matrix, aligned also to an explanatory power of 65.98% with regard to variability. The Confirmatory factor analysis also means by the high values resulting from the results of the commonalities and factor loadings condition assume that the data are robust and reliable. The results indicate that for the constructs Emotional Exhaustion, the moderate and high frequencies add up to 55%, surpassing the low frequency scale. For Cynicism, the scores indicate that moderate and high frequencies add up to 68%, surpassing the low frequency scale. For the last construct Professional Effectiveness, moderate and low frequencies add up to 66%, surpassing the high frequency scale. By the scores measured in this research, indicators for Burnout Syndrome are observed in the three constructs, being Emotional Exhaustion and Cynicism in moderate and high levels and Professional Efficacy with moderate and low graduation. It is concluded that the results indicate for Burnout Syndrome that should be analyzed by professional in health areas.